Nonlinear Seismic Response Based on Different Site Types: Soft Soil and Rock Strata - Meng Xiao; Jie Cui; Ya-dong Li; Van-Quang Nguyen (Advances in Civil Engineering)
Site condition is an important part of urban underground space development and construction. The seismic fortification of the site plays an important role in the safety of the whole project. To study the seismic dynamic response of the site under different geological conditions, seismic waves of different intensities (Chichi wave and Kobe wave) were input to a rock site with good geological conditions and a soft soil site, respectively. In this paper, the dynamic responses of these two types of free sites were calculated and analyzed using DEEPSOIL numerical simulation software. The dynamic responses of different types of sites under strong shock and persistent earthquakes are discussed under the equivalent linear and nonlinear conditions, and the related dynamic parameters are studied. The results show that the equivalent linear method is more effective than the nonlinear method, especially in the calculation of the strong nonlinear soft soil response induced by strong earthquakes. The amplification effect is more obvious in rock layer sites under strong earthquakes, and the “weakening” effect of soft soil sites is more obvious. Arias’s strength values show that both types of sites are safe under the incident of the two waves, but soft soil sites have better seismic performance. The results calculated by the equivalent linear method are larger and more unsafe; in particular, in the case of a strong earthquake with a stronger nonlinear Kobe wave, the results are more inaccurate. The purpose of this study is to provide a reference for seismic design and reinforcement measures of underground engineering.